2022
DOI: 10.1590/1678-4324-2022210841
|View full text |Cite
|
Sign up to set email alerts
|

Age-Stage, Two-Sex Life Tables of the 24 Spot Ladybird [(Subcoccinella vigintiquatuorpunctata (Coleoptera: Coccinellidae)]

Abstract: The life cycle of Subcoccinella vigintiquatuorpunctata (L.) (Coleoptera: Coccinellidae), which is an important pest of alfalfa (Medicago sativa Linnaeus (Fabales: Fabaceae) has been studied in laboratory conditions with a constant temperature of 25±1 ºC, relative humidity of 65±2% and light period of 16:8 hours. TWOSEX-MSChart was used to determine the parameters of the life table. The development stages of the egg to adult were recorded separately according to sex (female/male). The development duration of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The differences in the Si content could be the result of the insect dietary preferences. Considering that S. vigintiquatuorpunctata is a polyphagous herbivore, mainly feeding on species from Poaceae, Caryophyllaceae, Solanaceae, Malvaceae, Polygonaceae, and Fabaceae, it is likely that Si was acquired from its food source [ 22 , 55 , 56 ]. The amount of Si varies among plant species, with the highest concentration found in Poales [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in the Si content could be the result of the insect dietary preferences. Considering that S. vigintiquatuorpunctata is a polyphagous herbivore, mainly feeding on species from Poaceae, Caryophyllaceae, Solanaceae, Malvaceae, Polygonaceae, and Fabaceae, it is likely that Si was acquired from its food source [ 22 , 55 , 56 ]. The amount of Si varies among plant species, with the highest concentration found in Poales [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides preying on various insects, H. axyridis is also known to feed on fruits, vegetables, and pollen when primary food sources become scarce [ 20 , 21 ]. In contrast, Subcoccinella vigintiquatuorpunctata (L., 1758) , the 24-spot ladybird, is an important pest of Medicago sativa (L., 1753) [ 22 , 23 ]. When feeding upon host plant leaves, it produces characteristic damages by eating the lower layers of leaves’ epidermis and parenchyma, while the top layer remains in a membrane state.…”
Section: Introductionmentioning
confidence: 99%
“…Larvae and adults of 24-spot ladybird, Subcoccinella vigintiquatuorpunctata (L.) (Coleoptera: Coccinellidae), feed on the leaves of host plants. They eat the lower epidermis and parenchyma of the leaves, whereas the upper epidermis remains in the form of a membrane (Barış, 2021;Barış, 2022). The damaged leaves appear in the form of lace, which can cover the whole plant under severe infestation.…”
Section: Introductionmentioning
confidence: 99%
“…The larvae and adults of G. fornicata cause significant yield losses in alfalfa. Barış (2021) reported that larvae and adults feed on young shoots, leaf buds, flowers, leaves and the tips of alfalfa stems. The alfalfa leaf beetle was firstly reported by Alkan (1946) in Türkiye.…”
Section: Introductionmentioning
confidence: 99%